2012
DOI: 10.1111/j.2042-3292.2012.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anthelmintic efficacy against equine cyathostomins and Parascaris equorum in France

Abstract: Summary This article reports the results of a faecal egg count reduction test on 4 farms in France, as an integrated part of the routine deworming strategy against horse cyathostomins and Parascaris equorum. Treatment with fenbendazole (FBZ) or ivermectin (IVM) was evaluated in yearlings on Farms 1 and 2 and treatment with pyrantel embonate (PYR) was tested on Farms 3 and 4. Calculation of the arithmetic mean faecal egg count reduction and the 95% confidence intervals (95% CI) around the mean was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The main supposed reason of the ineffectiveness of treatments is the development of anthelmintic resistance in strongyle populations or the low exposure of mucosal larvae to many anthelmintic drugs (Love, 2003;Corning, 2009;Lyons et al, 2011a;Geurden et al, 2013). The belief that anthelmintic treatments are often ineffective in controlling strongyle infections due to a low exposure of mucosal larvae is not confirmed by our results, since mucosal larvae additional mortality of 80% changes only slightly the output of the models Fig.…”
Section: Discussionmentioning
confidence: 55%
“…The main supposed reason of the ineffectiveness of treatments is the development of anthelmintic resistance in strongyle populations or the low exposure of mucosal larvae to many anthelmintic drugs (Love, 2003;Corning, 2009;Lyons et al, 2011a;Geurden et al, 2013). The belief that anthelmintic treatments are often ineffective in controlling strongyle infections due to a low exposure of mucosal larvae is not confirmed by our results, since mucosal larvae additional mortality of 80% changes only slightly the output of the models Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Some studies have reported good efficacy of fenbendazole against ascarid populations that were resistant to ivermectin (Hearn and Peregrine ; Geurden et al . ). Thus, the situation for the benzimidazoles is similar to that of the pyrantel salts.…”
Section: Anthelmintic Treatmentmentioning
confidence: 97%
“…Signs of fenbendazole resistance have been reported in single studies from the USA (Lyons et al 2008) and Australia (Armstrong et al 2014). Some studies have reported good efficacy of fenbendazole against ascarid populations that were resistant to ivermectin (Hearn and Peregrine 2003;Geurden et al 2013). Thus, the situation for the benzimidazoles is similar to that of the pyrantel salts.…”
Section: Anthelmintic Treatmentmentioning
confidence: 99%
“…Anthelmintic resistance (AR) is generally defined as ‘when a previously effective drug is unable to kill the parasite population while exposed to therapeutic doses (Jabbar et al ., 2006) or loss of sensitivity to a drug in parasitic population that was sensitive to the same drug which is thought to be genetically transmitted (Kohler, 2001)’. AR has been documented in parasites of different animal species including cattle (Lifschitz et al ., 2010; Geurden et al ., 2015), sheep and goats (Coles, 2005; Domke et al ., 2012) and horses (Geurden et al ., 2013; Wolf et al ., 2014; Saes et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%